Proliferation Increasing Genetic Engineering in Human Corneal Endothelial Cells: A Literature Review - Arras, Wout; Vercammen, Hendrik; Ní Dhubhghaill, Sorcha; Koppen, Carina; Van den Bogerd, Bert (Frontiers in Medicine, 2021)
The corneal endothelium is the inner layer of the cornea. Despite comprising only a monolayer of cells, dysfunction of this layer renders millions of people visually impaired worldwide. Currently, corneal endothelial transplantation is the only viable means of restoring vision for these patients. However, because the supply of corneal endothelial grafts does not meet the demand, many patients remain on waiting lists, or are not treated at all. Possible alternative treatment strategies include intracameral injection of human corneal endothelial cells (HCEnCs), biomedical engineering of endothelial grafts and increasing the HCEnC density on grafts that would otherwise have been unsuitable for transplantation. Unfortunately, the limited proliferative capacity of HCEnCs proves to be a major bottleneck to make these alternatives beneficial. To tackle this constraint, proliferation enhancing genetic engineering is being investigated. This review presents the diverse array of genes that have been targeted by different genetic engineering strategies to increase the proliferative capacity of HCEnCs and their relevance for clinical and research applications. Together these proliferation-related genes form the basis to obtain a stable and safe supply of HCEnCs that can tackle the corneal endothelial donor shortage.